Efl Students' Perceptions Of Using Wattpad For Enhancing Creative Writing Skills - Siti Rachmah; Sholihatul Hamidah Daulay; Achmad Ramadhan (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study assessed EFL (English as a Foreign Language) students' perceptions of using Wattpad to improve their creative writing skills. Wattpad, a community-based platform, allows students to read, write, and share stories, which helps them develop creativity, narrative structure, and vocabulary. This research was conducted on 10 EFL student participants at the North Sumatra State Islamic University (UIN-SU), using a phenomenological approach. Data was collected through in-depth interviews to understand the experiences, benefits and challenges students face in using Wattpad for creative writing. This research aims to explore how social interaction and feedback from the Wattpad community contribute to the motivation and development of students' writing skills, particularly in terms of narrative ability, creativity, and character development. In addition, this research also aims to identify the challenges students face in using Wattpad and investigate how this platform can be optimized in classroom learning settings for EFL. The research results show that Wattpad provides significant benefits, especially in increasing student motivation through feedback and interaction with the community. Students reported improvements in their narrative techniques, creativity, and character development. However, challenges such as lack of technical guidance in creative writing and difficulties in time management were also cited by participants. In conclusion, Wattpad has proven to be an effective tool for supporting creative writing, especially if incorporated into the curriculum with proper guidance. This research suggests that further research should be carried out to optimize the use of Wattpad in learning and overcome the challenges faced by students.